LIMITATION OF TRADE MARGINS AS A MEASURE OF FOOD PRICE CONTROLS: EXPERIENCE OF SERBIA - Radukić, Snežana; Marković, Milan (Economics of Agriculture, 2015)
The aim of this study is to examine the influence of trade margins limitations to the prices of basic food products and general price level in the Republic of Serbia. Assessing the effects of the Regulation on the margins limitations from 2012, this paper considers the purpose of applying this instrument of indirect price control. In practice, prescribing a maximum trade margins can have positive effects on the food market stability only in the short term. It is therefore necessary a broader consideration of the factors of pricing on the food market and food inflation regulation by economic policy measures. A particular problem is the low degree of competition in the trade sector, which significantly affects the prices of the final products. Food price movements are very unstable, while their share in the consumer price index in the Republic of Serbia is significantly. It is logical to conclude that food prices have a dominant influence on inflation, so that the government actions in this area are justified.